Adverse Childhood Experiences in Trainees and Physicians With Professionalism Lapses: Implications for Medical Education and Remediation. (6th September 2020) - Williams, Betsy White; Welindt, Dillon; Hafferty, Frederic W.; Stumps, Anna; Flanders, Philip; Williams, Michael V.
Abstract : Purpose: Unprofessional behavior, which can include failure to engage, dishonest and/or disrespectful behavior, and poor self-awareness, can be demonstrated by medical trainees and practicing physicians. In the authors' experience, these types of behaviors are associated with exposure to adverse childhood experiences (ACEs). Given this overlap, the authors studied the percentage of ACEs among trainees and physicians referred for fitness-for-duty evaluations and patterns between the types of ACEs experienced and the reason for referral. Method: A final sample of 123 cases of U.S. trainees and physicians who had been referred to a Midwestern center for assessment and/or remediation of professionalism issues from 2013 to 2018 was created. Included professionalism lapses fell within 3 categories: boundary violation, disruptive behavior, or potential substance use disorder concerns. All participants completed a psychosocial developmental interview, which includes questions about ACE exposure. Overall rate of reported ACEs and types of ACEs reported were explored. Results: Eighty-six (70%) participants reported at least 1 ACE, while 27 (22%) reported 4 or more. Compared with national data, these results show significantly higher occurrence rates of 1 or more ACEs and a lower occurrence rate of 0 ACEs. ACEs that predicted reasons for referral were physical or sexual abuse, feeling unwanted or unloved, witnessing abuse of their mother or stepmother, or caretaker substance use. Conclusions: In this sample, ACE exposure was associated with professionalism issues. Remediating individuals with professionalism issues and exposure to ACEs can be complicated by heightened responses to stressful stimuli, difficulties with collaboration and trust, and decreased self-efficacy. Adoption of a trauma-informed medical education approach may help those that have been impacted by trauma rebuild a sense of control and empowerment. The findings of this study may be useful predictors in identifying those at risk of problematic behavior and recidivism before a sentinel event.